A Review of Interior Layout and Furniture Fit out Strategies of Bringing Greenery Indoors - Ikmal ‘Arief Niyazi Che Razi; Norzalifa Zainal Abidin (Cultural Syndrome, 2021)
Interior design is a of study of designers in crafting spaces that anticipate human needs and appeal to their emotions while pulling from a broad set of skills and technical knowledge. Recently, Green building development has become a worldwide popular topic in building industry. As an indispensable phase of a building project, interior decoration has an unavoidable impact on the environment and public health. Currently, there have been several green building evaluation standards for interior decoration. However, there is no specific evaluation standard, which is complied with the domestic situation of Malaysia, for green interior decoration. This study aims to develop an assessment standard for green interior decoration in the context of Malaysia. To start with, a compilations review of existing green interior building rating tools and focus group were held to filter the assessment items and to determine the basic framework of the proposed assessment standard. It applies not only on the availability of green product but also applies in term of interior spaces form, spatial layout and also in the application of furniture.